The Language Environment in Supporting Arabic Language Learning in Pesantren South Sulawesi - Muhammad Yusuf; Sri Mulya Rahmawati; Zulaeha Zulaeha (CV. Creative Tugu Pena, 2023)
This study aims to identify the reasons behind creating a language environment at the Darul Huffadh Islamic Boarding School in Bone. It also describes the model for designing language environment. This research used qualitative research with data collection techniques, including observation, interview, and documentation. The results showed that the creation of language environment at the Darul Huffadh was motivated and combined two academic contents, namely tahfidzul Qur'an and Kulliyah al-Mu'allimin al-Islamiyyah (KMI). The various subjects taught in the classroom are generally Arabic and fiqh lessons using the al-Dzikro book written by the founder of the Darul Huffadh, KH. Lanre Said and English lessons. The students are motivated to know and master Arabic in addition to understanding the Qur'an and Hadith, as well as to understand various Islamic subjects and books in PPDH. The models for creating language environment at the Darul Huffadh in general are: carrying out ilqo' al-mufradat, al-muhadathah, syu'bah, holding tajassus for students who speak Indonesian and regional languages, qiraatu al-Nasyrah, install Arabic vocabulary and install asalib in every place. As for the role of language environment in Arabic learning, in general, it can be declared successful in achieving the planned goals, namely increasing the students' Arabic proficiency. Therefore, designing the language environment can be applied as a step to improve students’ language competence. Keywords: Language Environment, Arabic Proficiency, Arabic Learning